2019
DOI: 10.7150/ijbs.33881
|View full text |Cite
|
Sign up to set email alerts
|

FZD2 regulates cell proliferation and invasion in tongue squamous cell carcinoma

Abstract: Many studies have shown that FZD2 is significantly associated with tumor development and tumor metastasis. The purpose of the present study was to gain insight into the role of FZD2 in the cell proliferation and invasion of tongue squamous cell carcinoma. According to TCGA-HNSC dataset, among the 10 Frizzled receptors, FZD2 exhibited the highest degree of differential expression between cancer tissues and normal tissues, and the overall survival of patients with higher FZD2 levels was shown to be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Each member of FZDs can activate WNT signaling pathway through interacting with different WNT proteins [3]. As previously reported, FZD2 is dysregulated in various cancer types, such as oral squamous cell carcinoma [4]{Asano, 2017 #3793}, gastric cancer [5], endometrial cancer [6], hepatocellular carcinoma [7] and tongue squamous cell carcinoma [8]. There is also a study reported that FZD2 suppresses tumor growth in salivary adenoid cystic carcinoma [9].…”
Section: Introductionmentioning
confidence: 82%
“…Each member of FZDs can activate WNT signaling pathway through interacting with different WNT proteins [3]. As previously reported, FZD2 is dysregulated in various cancer types, such as oral squamous cell carcinoma [4]{Asano, 2017 #3793}, gastric cancer [5], endometrial cancer [6], hepatocellular carcinoma [7] and tongue squamous cell carcinoma [8]. There is also a study reported that FZD2 suppresses tumor growth in salivary adenoid cystic carcinoma [9].…”
Section: Introductionmentioning
confidence: 82%
“…FZDs are reported to be involved not only in embryogenesis and development but also in tumor development and progression [ 9 , 10 ]. FZD2 was over-expressed in hepatocellular carcinoma (HCC) and head and neck squamous cell carcinoma compared to paracancerous tissues and significantly associated with the survival of patients [ 11 ]. In endometrial cancer, FZD2 could modulate the EMT process by activating Wnt signaling pathway [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FZD2 is up-regulated in many types of cancers, which is considered to be a new predictor of tumor recurrence. It is involved in the metastasis of various cancers including endometrial cancer (14), neuroblastoma (15), oral squamous cell carcinoma (16), tongue squamous cell carcinoma (17), hepatocellular carcinoma (18), colon cancer (19), and prostate cancer (20,21). Recently, the down-regulation of miR-30a-3p/5p was reported to promote ESCC cell proliferation through the up-regulation of WNT2 and FZD2, respectively (7).…”
Section: Introductionmentioning
confidence: 99%